2017
DOI: 10.1016/j.chom.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enterica Remodels the Host Cell Endosomal System for Efficient Intravacuolar Nutrition

Abstract: Salmonella enterica is a facultative intracellular pathogen that survives and proliferates in the Salmonella-containing vacuole (SCV), yet how these vacuolar bacteria acquire nutrition remains to be determined. Intracellular Salmonella convert the host endosomal system into an extensive network of interconnected tubular vesicles, of which Salmonella-induced filaments (SIFs) are the most prominent. We found that membranes and lumen of SIFs and SCVs form a continuum, giving vacuolar Salmonella access to various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
126
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(135 citation statements)
references
References 35 publications
4
126
0
Order By: Relevance
“…However, it is still unknown whether Salmonella-induced tubules play a role in pathogenesis. A recent study by Liss et al (2017) showed that Salmonella-induced tubules and SCVs form an extensive vacuolar continuum that allows rapid access of Salmonella to nutrients, thus promoting intracellular replication. These facts have raised doubt about the physiological role of tubules.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is still unknown whether Salmonella-induced tubules play a role in pathogenesis. A recent study by Liss et al (2017) showed that Salmonella-induced tubules and SCVs form an extensive vacuolar continuum that allows rapid access of Salmonella to nutrients, thus promoting intracellular replication. These facts have raised doubt about the physiological role of tubules.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the precise activation of SPI-2 genes within macrophages is essential for S. Typhimurium virulence. In addition to contributing to the SCV formation, SPI-2 also plays an important role in acquisition of nutrition and bacterial replication within macrophages (Figueira, Watson, Holden, & Helaine, 2013;Liss et al, 2017). In addition to contributing to the SCV formation, SPI-2 also plays an important role in acquisition of nutrition and bacterial replication within macrophages (Figueira, Watson, Holden, & Helaine, 2013;Liss et al, 2017).…”
mentioning
confidence: 99%
“…Typhimurium rapid access to endocytosed materials. Liss et al (2017) also demonstrated that intravacuolar S . Typhimurium connected to the SIF network are significantly more metabolically active than S .…”
Section: Sifs Link Salmonella To the Endocytic And Exocytic Pathwaysmentioning
confidence: 91%
“…Typhimurium can gain access to endocytosed nutrients (Popp et al, 2015). It was recently reported that membrane components and luminal content of the SIF network are both connected to, and interchanging with, the SCV in a SPI2-T3SS-dependent manner (Krieger et al, 2014; Liss et al, 2017), allowing S . Typhimurium rapid access to endocytosed materials.…”
Section: Sifs Link Salmonella To the Endocytic And Exocytic Pathwaysmentioning
confidence: 99%